Safety of EndoAnchors in real-world use: A report from the Manufacturer and User Facility Device Experience database - Masoomi, Reza (Vascular, 2019)
OBJECTIVES: A hostile proximal neck anatomy is the most common cause of abdominal aorta endovascular aneurysm repair failure leading to a higher risk of device migration, proximal type I endoleak, and subsequent open surgical repair. Endostapling is a technique to attain better fixation of the endograft to the aortic wall, and the only available device in the USA is Aptus Heli-FX EndoAnchor system (Medtronic Vascular, Santa Rosa, CA, USA). Preliminary data have shown efficacy and safety of its use, and the aim of this study is to assess device-related adverse events in real-world clinical use. METHODS: We quarried data from the publicly available Manufacturer and User Facility Device Experience database to identify Aptus Heli-FX EndoAnchor system-related adverse reports in endovascular aneurysm repair since FDA approval till August 31, 2017. An estimate of total devices implanted in the United States was quoted around 7,000 (Medtronic marketing internal data). RESULTS: Our query identified 229 separate reports, of which there were 85 adverse events (1.2% of the estimated EndoAnchor systems used). The most common adverse events were device dislodgement/fracture (65) and applicator malfunction (20). CONCLUSION: In early post-FDA approval use in a real-world setting, the EndoAnchor system is associated with a low rate of adverse events. Device dislodgement and embolization remain the most common adverse events. With increasing use of these devices in more difficult anatomy, careful patient selection and careful attention to technique may help to reduce these events even further.